Ukrainian journalist Yuri Butusov films himself firing a 152mm howitzer at "Russian occupiers" (Donbass Insider, 2021)
Ukrainian journalist Yuri Butusov has published a video of himself firing a howitzer at the "Russian occupiers" (i.e. in the Donbass).